2021
DOI: 10.3390/nu13020448
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns in Runners with Gastrointestinal Disorders

Abstract: Individuals with inflammatory bowel disease (IBD), irritable bowel syndrome (IBS) and reflux frequently experience gastrointestinal symptoms (GIS), potentially enhanced by high-intensity running. Food avoidances, food choices, and GIS in runners with IBS/IBD (n = 53) and reflux (n = 37) were evaluated using a reliability and validity tested questionnaire. Comparisons to a control group of runners (n = 375) were made using a Fisher’s Exact test. Runners with IBS/IBD experienced the greatest amount of exercise-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Some of the common ailments among athletes are stomach pain/cramps, bloating, intestinal pain/cramps and diarrhea (Erdman et al, 2021). However, since there is no evidence about the benefits of gastrointestinal stress, immune response and athletic performance, a gluten-free diet should not be recommended to athletes who do not have celiac disease (Lis et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the common ailments among athletes are stomach pain/cramps, bloating, intestinal pain/cramps and diarrhea (Erdman et al, 2021). However, since there is no evidence about the benefits of gastrointestinal stress, immune response and athletic performance, a gluten-free diet should not be recommended to athletes who do not have celiac disease (Lis et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, anaerobic strength exercise has higher adverse effects than aerobic endurance exercise [37,39]. Vigorous exercise, such as competitive running, can impair brain-gut axis signaling, trigger splanchnic ischemia and blood hypoperfusion where blood is moved forward the working muscles, exacerbating nutrient absorption, increasing intestinal permeability and motility dysfunction, and aggravating the severity of IBS GI and extra-GI symptoms [68][69][70][82][83][84][85][86]. Running works against the organized structure of the intestinal tract inside the abdominal cavity by gravity force which may lead to diaphragm spasm, dysbiosis, an increase of serotonin production, affects pain sensitization of afferent nerves, and induce IBS symptoms [85,89].…”
Section: How Substantial Is the Evidence Linking Exercise And Irritab...mentioning
confidence: 99%
“…In a study by Ruiz-Iglesias et al, 2022 [92] intensive training program in Wistar rats decreased the salivary IgA concentration, impaired the CLDN and ZO-1 gene expression, and altered the mesenteric lymphocyte composition. Increasing exercise intensity is associated with the activation of the sympathetic nervous system, releasing of stress hormones, decreasing of natural killer (NK) cells, and stimulation of pro-inflammatory modulators such as TNF-α, IL-1, IL-6, Interleukin-1 receptor antagonist, LPS translocation, and Tolllike receptors (TLR)-mediated recognition of gut commensal bacteria, which alters gut motility and leads to immunosuppression, localized and systemic inflammation [84,89,94]. Furthermore, vigorous repetitive exercise causes cellular damage, may compromise the mesenteric redox environment by weakening the activity of antioxidant enzymes and produces oxidation markers ROS, and leads to unfavorable intracellular biochemical changes [90,95], such as macromolecules peroxidation and ZO-1 phosphorylation [90].…”
Section: How Substantial Is the Evidence Linking Exercise And Irritab...mentioning
confidence: 99%
“…Comparably, evidence exists supporting the potential benefit of some dietary strategies, such as diets low in fermentable oligosaccharides, disaccharides, monosaccharides, and polyols, for reducing exercise-induced GIS [47]. While investigating the dietary patterns of both runners diagnosed with IBS and undiagnosed with IBS but suffering reflux frequently, [48] found that while many athletes avoid triggering foods in pre-race meals, they also consume foods that are potentially aggravating their GIS and would likely benefit from further nutritional advice for those suffering with IBS or IBS-related symptoms.…”
Section: Introductionmentioning
confidence: 99%